2005
DOI: 10.1590/s1415-47572005000300021
|View full text |Cite
|
Sign up to set email alerts
|

Dose assessment by quantification of chromosome aberrations and micronuclei in peripheral blood lymphocytes from patients exposed to gamma radiation

Abstract: Scoring of unstable chromosome aberrations (dicentrics, rings and fragments) and micronuclei in circulating lymphocytes are the most extensively studied biological means for estimating individual exposure to ionizing radiation (IR), which can be used as complementary methods to physical dosimetry or when the latter cannot be performed. In this work, the quantification of the frequencies of chromosome aberrations and micronuclei were carried out based on cytogenetic analyses of peripheral blood samples from 5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
1
10
0
3
Order By: Relevance
“…cervical cancer, prostate cancer or Hodgkin's disease. The doses estimated by MN analysis agree quite well with averaged whole body doses calculated from the radiation treatment plans (8,(42)(43)(44)(45). Studies performed in thyroid cancer patients undergoing radioiodine treatment further demonstrated that the CBMN assay is sensitive enough to detect low average whole-body doses from internal exposure scenarios (16,23,46).…”
Section: Applications Of the Cbmn Assay For Biological Dosimetrysupporting
confidence: 57%
“…cervical cancer, prostate cancer or Hodgkin's disease. The doses estimated by MN analysis agree quite well with averaged whole body doses calculated from the radiation treatment plans (8,(42)(43)(44)(45). Studies performed in thyroid cancer patients undergoing radioiodine treatment further demonstrated that the CBMN assay is sensitive enough to detect low average whole-body doses from internal exposure scenarios (16,23,46).…”
Section: Applications Of the Cbmn Assay For Biological Dosimetrysupporting
confidence: 57%
“…The number of MN in PBMCs of endometrial patients increased significantly after each RT fraction that we examined. Similarly, Silva-Barbosa et al assessed five uterine cancers patients irradiated by the absorbed dose of 0 Gy, 0.08 Gy, and 1.8 Gy, respectively, and found statistical increase in DC and MN, respectively [ 29 ]. A significant work has been conducted in the area of MN analysis and high-throughput biodosimetry by Dr. Brenner’s group [ 30 , 31 ], who recently reported an implementation of commercial robotic high-throughput screening system for large-scale radiological incidents [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Por exemplo, trabalhadores expostos ocupacionalmente a substâncias como benzeno e outros solventes orgânicos têm uma maior incidência de aberrações cromossômicas em comparação à população em geral 8 . Essas alterações citogenéticas são também utilizadas como indicadores de efeitos precoces nos estudos de monitoramento biológico em populações expostas a diversos agentes genotóxicos 7,10 , como verificado em (poucos) estudos brasileiros [55][56][57][58][59][60][61][62][63][64][65] .…”
Section: ▄ Discussãounclassified